Prevalence of work-related musculoskeletal disorder and its associated factors among weavers in low- and middle-income countries: a systematic review and meta-analysis - Belay Desye; Chala Daba; Abebe Kassa Geto; Gete Berihun; Leykun Berhanu (BMJ Open)
Objective This systematic review and meta-analysis aimed to determine the pooled prevalence of and factors associated with work-related musculoskeletal disorders (WMSDs) among low- and middle-income countries.Methods and design Databases such as PubMed/MEDLINE, CINAHL, LIVIVO, African Journals Online, African Index Medicus (AIM), HINARI, Science Direct, Web of Science, Cochrane Library, Google Scholar, Semantic Scholar and Google were used to retrieve all the relevant articles. The search was carried out from 22 April 2024 to 26 June 2024. Data were analysed via STATA 17 software. With a 95% CI, this meta-analysis with a random-effects model was carried out to determine the pooled prevalence.Setting The study was conducted in low- and middle-income countries.Participants Weavers of low- and middle-income countries.Outcome measures The primary outcome of this study was the prevalence of WMSD.Result In this meta-analysis, a total of 21 articles with 7322 study participants were included. The pooled prevalence of WMSDs was 72.20%. Working more than 8 hours per day, working in a chair with no back support, working in an uncomfortable posture, not performing regular physical exercise, lacking knowledge of the causes of WMSD and lacking job satisfaction were factors significantly associated with WMSDs.Conclusion A high prevalence of WMSDs among weavers in low- and middle-income countries was recorded. This indicates the need to take effective intervention measures. Rigorous ergonomic training, providing lengthy breaks and building centres for physical exercise, improving workplace ergonomic design and increasing job satisfaction are recommended.PROSPERO registration number CRD42024561064.